ANALYSIS OF CARBON MONOXIDE GAS DILUTION IN DEVELOPING FRONT USING HORIZONTAL DRIFT MODEL LABORATORY SCALE - Wisnu Harnoko (NIM : 12114020), Addien
Underground mines have a greater risk of danger compared to open mines, due to limited conditions and limited work locations in underground mines. Potential hazard that often occur in underground mining are dangerous and toxic gases, such as carbon monoxide (CO) which is often found in underground mines. This gas is very toxic because the bonding strength of carbon monoxide to hemoglobin is 250 times faster than oxygen bonding to hemoglobin. This study aims to determine the distribution of CO in the test using a horizontal drift acrylic model. In addition, the diffusion coefficient of CO is determined based on the Taylor diffusion coefficient equation (1954) empirically (E) along the straight drift path with a square opening form represented by a physical scale laboratory model. We also estimate the effect of the test condition parameters such as the comparison of the duct distance to the face (x/D) and the Reynolds number (Re') on the results of the diffusion coefficient (E). The procedure includes CO sampling and calibrated with the MQ-7 sensor then proceed with gas dilution testing with the horizontal drift model. The results from CO distribution show the highest measurement of gas concentration due to the distance of the sensor (L3/D) which is far from the face so that the readable gas concentration is higher. The closer the measurement point (L1/D), the greater the value of the diffusion coefficient. Conversely, if the farther the measurement point (L3/D), the value of the diffusion coefficient will be smaller. The distance of duct to face (x/D) does not affect the value of the diffusion coefficient (E), but the value of the diffusion coefficient will affect the Reynolds number (Re'). The greater the value (Re ') then the value of E is also getting greater.